The Influence of Waste Tire Powder on the Properties of Waste Tire Powder/Polypropylene Plastic Composite - Ong, Huei Ruey; Wan Mohd Eqhwan, Iskandar; Emyra Ezzaty, Masiren; Khan, Md. Maksudur Rahman; Ridzuan, Ramli; Rohaya, Mohamed Halim; Muhammad Khairul Anuar, Mohamed (IOP Publishing, 2021)
The use of waste tire powder (WTP) as a polypropylene (PP) property enhancer in plastic composite has been prepared. Scanning electron microscopy (SEM), Fourier Transform Infrared Spectroscopy (FTIR) and mechanical testing have been used to measure the properties of PP/WTP. Sample morphology shows that there are no impurities in post-fracture images on both PP and PP/WTP. Apart from that, it can be seen that the surface of PP / WTP is slightly smooth. PP and PP/WTP are nearly similar in the FTIR spectrum. During tensile and flexural tests, the PP/WTP value drops as the WTP amount increases. For elongation break and impact testing, PP/WTP at 40% WTP exhibits highest strength value compare to other samples. In all cases, WTP with smallest range of size (250–500 µm) shows better mechanical performance compare to other sizes. PP/WTP plastic composite has a highly great potential to be used in most plastic manufacturing industry and sustain the green environment by taking the advantage of waste tire powder.